Microbial quality and constraints affecting of cow milk supply chain in Nekemte City, Ethiopia - Alemu Oli Tola; Habtamu Fekadu Gemede (Cogent Food & Agriculture)
Milk is one of the most common food sources in the human diet and is also a product that is directly available for consumption and contains numerous nutrients. Milk is a nutritious food for human beings, but it also serves as a good medium for the growth of many microorganisms. Hence, this study aimed to assess microbial quality and constraints affecting cow’s milk supply chains in Nekemte City, Ethiopia. The milk samples were collected from the supply chains morning and afternoon. The overall of microbial load in supply chain were 5.19 ± 0.78 (log10 cfu/ml), 4.54 ± 1.09 (log10 cfu/ml), 4.39 ± 1.04 (log10 cfu/ml), 4.21 ± 1.07 (log10 cfu/ml), 5.20 ± 0.85 (log10cfu/ml), 4.53 ± 1.06 (log10 cfu/ml) and 4.52 ± 0.91 (log10 cfu/ml) at Total bacterial count (TBC), Total coliform unit (TCC), Escherichia coli (E. coli), Salmonella, Staphylococcus, yeasts and molds, respectively. The major constraints affecting milk production and milk market in the supply chains were 20% shortage of animal feed and very expensive, 40% the price of milk seasonality, and 31.6% lack of training and awareness in supply chains. The study shows that there is an issue with supply chains and limits influencing cow’s milk, and that all available solutions should be implemented by all interested bodies to enhance microbiological quality towards milk hygiene, as well as to raise awareness and quality of life.